2002
DOI: 10.1016/s0886-3350(02)01369-x
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon experience and patient comfort during clear corneal phacoemulsification under topical local anesthesia

Abstract: Topical anesthesia with proparacaine provided similar and reasonable analgesic effects in patients having surgery by a surgeon in the learning curve and those having surgery by an experienced surgeon. The discomfort perceived during surgery performed by an experienced surgeon was less, although not statistically significantly different.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 12 publications
0
10
0
6
Order By: Relevance
“…Topical anesthesia provided similar and reasonable analgesic effects when performed by resident surgeons or experienced surgeons 35 ; however, this study is limited because patients were not asked to rate their discomfort and pain level during anesthesia administration and surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Topical anesthesia provided similar and reasonable analgesic effects when performed by resident surgeons or experienced surgeons 35 ; however, this study is limited because patients were not asked to rate their discomfort and pain level during anesthesia administration and surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Mathew et al , compared patient’s pain level and discomfort when operated upon by an experienced surgeon, versus a surgeon who was still in the learning curve. [18] He reported that topical anesthesia with Proparacaine provided similar and reasonable anesthetic effects in patients having surgery by a surgeon in the learning curve and those having surgery by an experienced surgeon. Although the discomfort perceived during surgery performed by an experienced surgeon was less, it was not statistically significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…When evaluating 46 patients undergoing phacoemulsification under topical anesthesia with proximetacaine without sedation, several authors observed that surgeons on the learning curve and experienced surgeons accepted well the technique with greater discomfort for less experienced surgeons especially due to ocular akinesia, but this was not statistically significant. Besides, the eye globe can be easily stabilized by using forceps or rings and by the simultaneous use of phaco and a second device by the technique of bimanual phaco [14][15][16] . Obtaining clear corneas in the first postoperative day is one of the greatest challenges in the surgical treatment of cataracts, i.e., trying to reduce as much as possible endothelial and incisional trauma during surgery 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Ao avaliar 46 pacientes submetidos à facoemulsificação sob anestesia tópica com proximetacaína sem sedação, alguns autores observaram que tanto cirurgiões na curva de aprendizagem como cirurgiões experientes aceitam bem a técnica, com um maior desconforto para os menos experientes, sobretudo por causa da cinesia ocular, porém sem significância estatística. Além disso, o globo ocular pode ser facilmente estabilizado pelo uso de fórceps ou anéis, pelo uso simultâneo do faco e de um segundo instrumento pela técnica de faco bimanual [14][15][16] . Um dos grandes desafios hoje no tratamento cirúrgico da catarata é a obtenção de córneas claras no primeiro dia de pós-operatório, ou seja, tentar reduzir ao máximo o trauma endotelial e incisional durante a operação 17 .…”
Section: Métodounclassified